La maison - Gitai, Amos; Aldama, Emanuel (Arte France, 2003)
"House" is the story of a house in West-Jerusalem: abandoned during the 1948 war by its owner, a Palestinian doctor; requisitioned by the Israeli government as "vacant"; rented to Jewish Algerian immigrants in 1956; purchased by a university professor who undertakes its transformation into a patrician villa ... The building site is like a theatre in which the former inhabitants, the neighbours, the workers, the builder and the new owner all appear. Israeli television censured the film. [www.amosgitai.com]
Keywords: DVD-Video